(untitled) (International conference on multidisciplinary science, 2025)
The concept of meronymy—the semantic link between pieces and wholes—is examined in this article. The phrase, which comes from Greek, shows how a meronym indicates a component and its holonym indicates the entire; for example, "leaf" is a part of a "tree." This link is known in Uzbek as "partonymy," highlighting the language’s relationship between parts and wholes. Examples of meronymy in both Uzbek and English are given in the paper. For instance, "house" has parts like doors and windows, whereas "body" has parts like arm, leg, and head. Understanding how languages convey part-whole relationships in diverse circumstances is improved by highlighting the complexity of meronymy and showing that different languages may represent these relationships in distinctive ways.